Novel asymmetrical azines appending 1, 3, 4-thiadiazole sulfonamide: synthesis, molecular structure analyses, in silico ADME, and cytotoxic effect. Issue 15 (3rd April 2023) - Bondock, Samir; Albarqi, Tallah; Shaaban, Ibrahim A.; Abdou, Moaz M.
Abstract : Toward finding potential and novel anticancer agents, we designed and prepared novel differently substituted unsymmetrical azine-modified thiadiazole sulfonamide derivatives using the "combi-targeting approach". Abstract : Toward finding potential and novel anticancer agents, we designed and prepared novel differently substituted unsymmetrical azine-modified thiadiazole sulfonamide derivatives using the "combi-targeting approach". An efficient procedure for synthesizing the designed compounds starts with 5-acetyl-3- N -(4-sulfamoylphenyl)-2-imino-1, 3, 4-thiadi-azoline 4 . The E / Z configuration for compound 5 was investigated based on spectral analysis combined with quantum mechanical calculation applying the DFT-B3LYP method and 6-31G(d) basis set. The computational results found that the E isomer was energetically more favorable than the Z isomer by 2.21 kcal mol −1 . Moreover, 1 H and 13 C chemical shifts for the E and Z isomers in DMSO were predicted using the GIAO-B3LYP/6-31G(d) computations and IEF-PCM solvation model. The computed chemical shifts for both isomers are consistent with those observed experimentally, indicating that they exist in the solution phase. Moreover, the E / Z configuration for the synthesized azines 7a–c, 9, 11, 13, 15a and 15b was also studied theoretically using the DFT-B3LYP/6-31G(d) calculations. In silico prediction for the biological activities was reported regarding the HOMO–LUMO energy gaps and molecular reactivity descriptors besides the ADMT/drug-likeness properties. The cytotoxic effect of the synthesized compounds has been assayed via the determination of their IC50 .